Selection of Biosurfactan/Bioemulsifier-Producing Bacteria From Hydrocarbon-Contaminated Soil - Viramontes-Ramos, Sabina (Sociedade Brasileira de Microbiologia, 2010)
Petroleum-derived hydrocarbons are among the most persistent soil contaminants, and some hydrocarbon-degrading microorganisms can produce biosurfactants to increase bioavailability and degradation. The aim of this work was to identify biosurfactant-producing bacterial strains isolated from hydrocarbon-contaminated sites, and to evaluate their biosurfactant properties. The drop-collapse method and minimal agar added with a layer of combustoleo were used for screening, and positive strains were grown in liquid medium, and surface tension and emulsification index were determined in cell-free supernantant and cell suspension. A total of 324 bacterial strains were tested, and 17 were positive for the drop-collapse and hydrocarbon-layer agar methods. Most of the strains were Pseudomonas, except for three strains (Acinetobacter, Bacillus, Rhodococcus). Surface tension was similar in cell-free and cell suspension measurements, with values in the range of 58 to 26 (mN/m), and all formed stable emulsions with motor oil (76-93% E(24)). Considering the variety of molecular structures among microbial biosurfactants, they have different chemical properties that can be exploited commercially, for applications as diverse as bioremediation or degradable detergents.